Analysis of The Influence of Product Quality and Company Image on Customer Satisfaction at Bank Bjb - Froilan Delute Mobo; Ujang Badru (Eastasouth Institute, 2022)
Customers are crucial in the existence of a bank. The customer can be said to be a feeling after the performance he perceives with his expectations. The performance perceived by customers of the expectations they want is an important measure of the satisfaction they feel. Customers can be one of the keys to the success of a bank. This writing uses a quantitative research approach. The focus of this research is the influence of product quality and corporate image on customer satisfaction. The location of this research was conducted at Bank BJB. Based on the discussion, 1) product quality has a positive and significant effect on customer satisfaction, 2) company image has a positive and significant effect on customer satisfaction, and 3) product quality and corporate image have a simultaneous effect on customer satisfaction.